2017
DOI: 10.1080/03007995.2017.1292229
|View full text |Cite
|
Sign up to set email alerts
|

The benefits, risks and costs of privacy: patient preferences and willingness to pay

Abstract: Patients were very willing to share medical information with their providers. They were able to see the importance of sharing medical information to provide the best possible care. They were unwilling to hide information from providers if there was increased medical risk. Patients were willing to spend additional time for privacy, but most were unwilling to spend extra money. Sixty-eight percent of patients favored reducing medical costs over privacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Patients also tend not to be willing to pay more for increased privacy. Trachtenbarg et al found that 95% of patients surveyed (n=834) would not restrict the information they share with providers, even for sensitive conditions like HIV, and that if given the choice, 68% of patients would put money toward reducing medical costs rather than improving privacy in healthcare 11. Even if we insist on a strong control regime for health data, it seems unlikely that patients will actually restrict access in a meaningful way.…”
Section: Why Control Is Inadequatementioning
confidence: 99%
“…Patients also tend not to be willing to pay more for increased privacy. Trachtenbarg et al found that 95% of patients surveyed (n=834) would not restrict the information they share with providers, even for sensitive conditions like HIV, and that if given the choice, 68% of patients would put money toward reducing medical costs rather than improving privacy in healthcare 11. Even if we insist on a strong control regime for health data, it seems unlikely that patients will actually restrict access in a meaningful way.…”
Section: Why Control Is Inadequatementioning
confidence: 99%
“…Sharing PHID ( Table 2 ) for primary purposes was reported to be highest in the case of USA patients with their treating physicians (95%), 57 and the lowest by another study that included USA public regarding sharing their data with their healthcare providers (49%). 58 One group of studies reported variability in sharing intentions depending on the data recipient, with findings indicating that healthcare providers that are in more direct relationships with the data donor/patient (such as doctors in charge, doctors they were referred to, healthcare providers working at the study sites), received higher support compared with other healthcare staff the participants have not encountered while receiving care.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that “social networks” or “social media” were topics often used in the 228 retrieved papers, many papers were not related to these topics after a close examination. The 15 candidate best papers are grouped according to the following areas: 1) privacy implications and data sharing for research (online recruitment, biobanking, and clinical trials data reuse) 3 4 5 ; 2) privacy concerns and use of personal health information 6 7 8 9 10 11 12 ; and 3) general considerations regarding portal use and individual characteristics 13 14 15 16 17 .…”
Section: Resultsmentioning
confidence: 99%